Mary Austin and the American West - Goodman, Susan, 1951- (University of California Press, 2008)
Mary Austin (1868-1934)-eccentric, independent, and unstoppable-was twenty years old when her mother moved the family west. Austin's first look at her new home, glimpsed from California's Tejon Pass, reset the course of her life, ""changed her horizons and marked the beginning of her understanding, not only about who she was, but where she needed to be."" At a time when Frederick Jackson Turner had announced the closing of the frontier, Mary Austin became the voice of the American West. In 1903, she published her first book, The Land of Little Rain, a wholly original look at the West's desert.